The effect of NiO addition on the grain boundary behavior and electrochemical performance of Gd-doped ceria solid electrolyte under different sintering conditions. Issue 1 (January 2017) - Xu, Dan; Li, Kehui; Zhou, Yongjun; Gao, Yang; Yan, Duanting; Xu, Shifeng
Abstract: It has been reported that some transition metal oxides are effective aids both for the densification and the grain boundary behavior of ceria-based electrolytes. In the present work, NiO which is the most popular component of the anode of solid oxide fuel cells was added directly into the electrolyte ceramic, Ce0.8 Gd0.2 O1.9, to investigate the effects of the presence of NiO on the properties of GDC electrolyte. All of the samples possess a single phase with cubic fluorite structure. The grain size is increased by the addition of NiO when the sintering temperature is 1400 °C. This modification in chemical composition also results in a decrease in activation energy and thus a tendency to enhance grain boundary mobility. The maximum power density of the composite electrolyte single cell is higher than that of a GDC single cell. Therefore, NiO can be used as an effective aid for ceria-based electrolytes.